Investigations of mechanisms of drug-resistance and associated biomarkers in HER2-overexpressing breast cancer - Breslin, Susan (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2016)
Breast cancer is the most commonly diagnosed cancer amongst women in Ireland. HER2-overexpressing breast cancer accounts for 25-30% of all breast cancer cases and was the focus of this project. While treatment options for breast cancer are continuously improving, the main issue with effective patient therapy is the development of drug resistance. Consequently, it is critical that the mechanisms that mediate resistance are understood. This was a major focus of this work. Additionally, identifying biomarkers that will successfully diagnose and predict patient response to therapy are also essential to improve disease management, an issue which was also addressed in this project.
Keywords: Pharmacy & Phamaceutical Sciences, Ph.D.; PhD Trinity College Dublin, 2016